2022
DOI: 10.1002/cncr.34229
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonitis after immune checkpoint inhibitor therapies in patients with acute myeloid leukemia: A retrospective cohort study

Abstract: Background Immune checkpoint inhibitors (ICI), combined with hypomethylating agents, can be used to treat acute myeloid leukemia (AML), but this strategy results in a high rate of pneumonitis. The authors sought to determine risk factors for pneumonitis development and whether pneumonitis increased mortality. Methods The authors conducted a retrospective review of 258 AML patients who received ICI‐containing regimens from 2016 to 2018. A multidisciplinary adjudication committee diagnosed pneumonia and pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Missing values were reported in 22/50 studies, the maximum proportion of missing values in a single-variable ranges between 0.2% and 64.7% across the studies (median:17.3%, IQR: 7.5%-36.1%). 4/22 of the studies included the missing values as a separate level in regression analysis ( 11 , 35 , 41 , 46 ), 5/22 were unclear about the imputation method used ( 19 , 21 , 39 , 61 , 64 ), the rest simply excluded subjects with missing values. None of the studies investigated whether the missing values were independent from values in other variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Missing values were reported in 22/50 studies, the maximum proportion of missing values in a single-variable ranges between 0.2% and 64.7% across the studies (median:17.3%, IQR: 7.5%-36.1%). 4/22 of the studies included the missing values as a separate level in regression analysis ( 11 , 35 , 41 , 46 ), 5/22 were unclear about the imputation method used ( 19 , 21 , 39 , 61 , 64 ), the rest simply excluded subjects with missing values. None of the studies investigated whether the missing values were independent from values in other variables.…”
Section: Resultsmentioning
confidence: 99%
“…Survival analysis was the second most popular method for univariate analysis, and was performed in 8/47 studies that conducted univariate analysis: 5/8 studies used survival analysis alone to identify risk factors (2 applied the Fine-Gray test, 3 applied Cox proportional hazard model) ( 40 , 46 , 53 , 61 , 63 ). One study conducted a contingency test and used a Cox proportional hazard model on the same factor ( 49 ), the other two used contingency and/or two-sample tests to select variables that should be further assessed in univariate survival modelling ( 39 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delaunay et al (2017) reported BAL findings in 35 samples from a cohort of 64 ICI-pneumonitis patients, and 68.5% of these patients have BAL lymphocytes > 15%. However, in a study by (Sheshadri et al 2022), lymphocytosis was not a distinctive feature of pneumonitis in patients with leukemia who underwent BAL. In addition, eosinophils were also found in some cases (Hara et al 2021).…”
Section: Bal Lymphocytosis May Be An Adjunct To Diagnosis Ici-pneumon...mentioning
confidence: 85%
“…An explanation for the differences in risk of ICI-related pulmonary irAEs is the possible variations in immune responses between both sexes. [ 20 ] The female sex is hypothesized to mount a stronger innate and adaptive immunity, resulting in less susceptibility to ICI-related irAEs than the male sex. [ 31 33 ] A retrospective study on ICI-related pneumonitis in patients with acute myeloid leukemia found it to be most remarkable in the male than in the female sex.…”
Section: Discussionmentioning
confidence: 99%